THE PLACE OF THE CONCEPT OF ETHICS IN THE TEACHINGS OF IMAM BUKHARİ IN THE DEVELOPMENT OF SOCIETY (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role of ethics in Imom Bukhari’s teachings in the context of societal development. The main focus is on his work “Al-Adab al-Mufrad,” which highlights ethical values and their impact on social stability and the importance of ethical behavior. The article also explores the relevance of Imom Bukhari's teachings in contemporary society.